Cleft from the Main: The Problem of Identity for the Women Writers in Margaret Laurence's The Diviners and Audrey Thomas' Intertidal Life. - Brendon, Carolyn (My University, 1991)
This thesis deals with the problem of identity for the protagonists, Morag and Alice, in Margaret Laurence's The Diviners and Audrey Thomas' Intertidal Life. Both women are writers searching for a self underneath the patriarchal fictions of womanhood. The notion of an essential self, Morag and Alice realize, is itself another fiction. What Morag and Alice discover in their self-reflective writings is only what they have been constituted as within the various discursive fields in which they participate. The self, these women come to recognize, is not an essence but rather a site at which various discourses converge and compete for sovereignty of the individual. In most cases, certain discourses, inconsistent though they may be, achieve dominance over other discourses and consequently over the subject, creating the illusion of a unified and coherent subjectivity. In the case of women writers, however, two contradictory discursive fields or ideologies are continually vying for mastery of the subject, each with considerable success. As women, Morag and Alice are inscribed within the field of traditional feminine discourses of submission and self-effacement, and as writers they are interpellated within liberal humanist discourses of gender equality. These two subject positions, woman and writer, are contradictory and thus conflict with one another. In attempting to unify their heterogeneous experiences of subjectivity, Morag and Alice recognize not only the impossibility of such a task, but also the arbitrary, conventional and ideologically-motivated nature of all discourse, which is to say of language and therefore of subjectivity itself. Having discovered this fact, Morag and Alice are then able to wrestle with language and unsettle the systems of symbols, analogies and metaphors constitutive of the dominant discourses and ideologies which have created a notion of woman which has validated her oppressed status.
Keywords: English Language and Literature; English Language and Literature